Investigation of Strong Strata Behaviors in the Close-Distance Multiseam Coal Pillar Mining - Hongwei Mu; Yongsheng Bao; Dazhao Song; Dongfang Su (Shock and Vibration)
According to the new stress distribution pattern and the strong strata behaviors as the characteristics of the coal pillars in the close-distance multiseam coal pillar mining, the common characteristics of different types of overlying coal pillars were summarized and analyzed. Moreover, a theoretical model for the mechanism of strong strata behaviors in the close-distance multiseam coal pillar mining was established, which was validated by the monitoring data of seismic computed tomography CT, microseism, and electromagnetic radiation (EMR). Furthermore, the results of the study indicated that the main factors affecting the strong strata behaviors were the static stress concentration caused by the overlying coal pillars and the dynamic disturbance caused by the fracturing and slipping of the overlying coal pillars and roof under the influence of mining. In the case of Xinzhouyao coal mine, the transmitted stress and lateral support pressure of the overlying coal pillars accounted for 78.3% and 16% of the vertical concentrated stress, respectively, and the areas closer to the overlying coal pillars were more susceptible to dynamic load disturbances. The monitoring results of seismic computed tomography CT and EMR demonstrated the static load stress concentration area was distributed near the overlying coal pillar, and the stress concentration degree was greater in the area of superimposed lateral support pressure and advanced support pressure. Moreover, microseismic spatial positioning revealed that the high-energy microseismic events were mainly concentrated near the overlying large coal pillars and roof. The on-site multiparameter detection results were highly consistent with the characteristics of actual strata behaviors and the conclusions of the theoretical model. This method could provide a reference for the quantitative calculation of stress distribution under similar conditions and the identification of the danger zone of strata behaviors.